Kelayakan Usaha dan Strategi Pengembangan Greenhouse Hidroponik Berbasis Pesantren - Akhmad Hidayat Nurul Akbar; Sani Haryati (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to assess the business feasibility and development strategy of a hydroponic greenhouse operated by the Suryalaya Islamic Boarding School in Tasikmalaya. A descriptive qualitative approach was applied through a single case study design, with data sourced from in-depth interviews, field observations, and a review of financial records for the first production cycle. The analysis includes a classification of cost structures, calculation of Cost of Goods Sold (COGS) using variable costing and full costing methods, evaluation of marketing channels, and formulation of a SWOT-based strategy. Key findings reveal that first-cycle expenditures are heavily dominated by one-time infrastructure investments, while recurring operational costs per cycle are significantly lower. The gap between full cost COGS and the prevailing selling price, primarily caused by amortization expenses in the initial operational phase, is expected to narrow significantly in subsequent cycles as fixed costs are spread over a longer production horizon. The marketing analysis identifies two channels with different price levels, indicating an untapped opportunity in the premium segment